Chimeric RNAs reveal putative neoantigen peptides for developing tumor vaccines for breast cancer - Mistretta, Brandon; Rankothgedera, Sakuni; Castillo, Micah; Rao, Mitchell; Holloway, Kimberly; Bhardwaj, Anjana; El Noafal, Maha; Albarracin, Constance; El-Zein, Randa; Rezaei, Hengameh; Su, Xiaoping; Akbani, Rehan; et al. (Frontiers in Immunology, 2023)
We present here a strategy to identify immunogenic neoantigen candidates from unique amino acid sequences at the junctions of fusion proteins which can serve as targets in the development of tumor vaccines for the treatment of breast cancer. We mined the sequence reads of breast tumor tissue that are usually discarded as discordant pairedend reads and discovered cancer specific fusion transcripts using tissue from cancer free controls as reference. Binding affinity predictions of novel peptide sequences crossing the fusion junction were This is a provisional file, not the final typeset article analyzed by the MHC Class I binding predictor, MHCnuggets. CD8+ T cell responses against the 15 peptides were assessed through in vitro Enzyme Linked Immunospot (ELISpot). We uncovered 20 novel fusion transcripts from 75 breast tumors of 3 subtypes: TNBC, HER2+, and HR+. Of these, the NSFP1-LRRC37A2 fusion transcript was selected for further study. The 3833 bp chimeric RNA predicted by the consensus fusion junction sequence is consistent with a read-through transcription of the 5'-gene NSFP1-Pseudo gene NSFP1 (NSF truncation at exon 12/13) followed by trans-splicing to connect with LRRC37A2 located immediately 3' through exon 1/2. A total of 15 different 8-mer neoantigen peptides discovered from the NSFP1 and LRRC37A2 truncations were predicted to bind to a total of 35 unique MHC class I alleles with a binding affinity of IC50<500nM.); 1 of which elicited a robust immune response. Our data provides a framework to identify immunogenic neoantigen candidates from fusion transcripts and suggests a potential vaccine strategy to target the immunogenic neopeptides in patients with tumors carrying the NSFP1-LRRC37A2 fusion.